A review: On the development of low melting temperature Pb-free solders - Kotadia, Hiren R.; Howes, Philip D.; Mannan, Samjid H. (Microelectronics and reliability, 2014)
Pb-based solders have been the cornerstone technology of electronic interconnections for many decades. However, with legislation in the European Union and elsewhere having moved to restrict the use of Pb, it is imperative that new Pb-free solders are developed which can meet the long established benchmarks set by leaded solders and improve on the current generation of Pb free solders such as SAC105 and SAC305. Although this poses a great challenge to researchers around the world, significant progress is being made in developing new solder alloys with promising properties. In this review, we discuss fundamental research activity and its focus on the solidification and interfacial reactions of Sn-based solder systems. We first explain the reactions between common base materials, coatings, and metallisations, and then proceed to more complex systems with additional alloying elements. We also discuss the continued improvement of substrate resistance to attack from molten Sn which will help maintain the interface stability of interconnections. Finally, we discuss the various studies which have looked at employing nanoparticles as solder additives, and the future prospects of this field.